Resistome, mobilome, and virulome explored in clinical isolates derived from acne patients in Egypt: unveiling unique traits of an emerging coagulase-negative Staphylococcus pathogen - Amer, Mai A.; Darwish, Manal M.; Soliman, Noha S.; Amin, Heba M. (Frontiers in Cellular and Infection Microbiology, 2024)
Coagulase-negative staphylococci (CoNS) are a group of gram-positive staphylococcal species that naturally inhabit the healthy human skin and mucosa. The clinical impact of CoNS-associated infections has recently been regarded as a challenge for diagnosis and therapeutic options. CoNS-associated infections are primarily caused by bacterial resistance to antibiotics and biofilm formation. As antibiotics are still the most used treatment, this problem will likely persist in the future. The present study aimed to investigate the resistance and virulence of CoNS recovered from various acne lesions and explore their genetic basis. Skin swab samples were collected from participants with acne and healthy skin. All samples underwent conventional culture for the isolation of CoNS, MALDI-TOF confirmation, antibiotic susceptibility, and biofilm formation testing. A total of 85 CoNS isolates were recovered from the samples and preliminarily identified as Staphylococcus epidermidis. Isolates from the acne group (n = 60) showed the highest rates of resistance to penicillin (73%), cefoxitin (63%), clindamycin (53.3%), and erythromycin (48%), followed by levofloxacin (36.7%) and gentamycin (31.7%). The lowest rates of resistance were observed against tetracycline (28.3%), doxycycline (11.7%), and minocycline (8.3%). CoNS isolated from mild, moderate acne and healthy isolates did not show strong biofilm formation, whereas the isolates from the severe cases of the acne group showed strong biofilm formation (76.6%). Four extensively drug-resistant and strong biofilm-forming staphylococcal isolates recovered from patients with severe acne were selected for whole-genome sequencing (WGS), and their genomes were investigated using bioinformatics tools. Three of the sequenced genomes were identified as S. epidermidis; however, isolate 29AM was identified as Staphylococcus warneri, which is a newly emerging pathogen that is not commonly associated with acne and was not detected by MALDI-TOF. All the sequenced strains were multidrug-resistant and carried multiple resistance genes, including blaZ, mecA, tet(K), erm(C), lnuA, vgaA, dfrC, fusB, fosBx1, norA, and vanT, which were found to be located on plasmids and chromosomes. Virulence features were detected in all genomes in the presence of genes involved in adherence and biofilm formation (icaA, icaB, icaC, sdrG, sdrH, atl, ebh, and ebp). Only the S. warneri isolate 29AM contained immune evasion genes (capB, capC, acpXL, and manA), an anti-phagocytosis gene (cdsA), and other unique features. As a result of their potential pathogenicity and antibiotic resistance, CoNS must be monitored as an emerging pathogen associated with acne infections. To the best of our knowledge, this is the first report to isolate, identify, and correlate S. warneri with severe acne infections among Egyptian patients using WGS and bioinformatic analysis.